On approximation of value functions for controlled discontinuous random processes - Danilenko, Svetlana; Pragarauskas, Henrikas (Mathematical Modelling and Analysis, 2011)
We consider the problem of approximation of value functions for controlled possibly degenerated diffusion processes with jumps by using piece-wise constant control policies. A rate of convergence for the corresponding value functions is established provided that the coefficients of controlled processes are sufficiently smooth. The paper extends the results of N.V. Krylov to a more general class of controlled processes.